Common variation at 3p22.1 and 7p15.3 influences multiple myeloma risk - Broderick, Peter (Nat Genet, 2011)
To identify risk variants for multiple myeloma (MM), we conducted a genome-wide association study totaling of 1,675 MM cases and 5,903 controls. We identified risk loci for MM at 3p22.1 (rs1052501, ULK4; odds ratio [OR]=1.32; P=7.47x10(-9)) and 7p15.3 (rs4487645, OR=1.38; P=3.33x10(-15)). In addition, we observed a promising association at 2p23.3 (rs6746082, OR=1.29; P=1.22x10(-7)). Our study reports previously unidentified genomic regions associated with MM risk that may lead to new etiological insights.